ENGLISH LANGUAGE NEEDS AND COMPETENCY GAPS OF NATIONAL NARCOTICS BOARD PERSONNEL IN GLOBAL PROFESSIONAL COMMUNICATION DEMANDS - Febri Haryanti; Akhyar Rido (Premise: Journal of English Education and Applied Linguistics, 2026)
This study aims to analyze the English language needs of National Narcotics Board personnel in the context of international cooperation and to identify gaps between their current English proficiency and global professional communication demands. The study employed a qualitative design involving ten personnel from various work units, with five participants selected for in-depth interviews. Data were collected through questionnaires and semi-structured interviews. The questionnaire gathered information on frequency of English use, self-assessed proficiency, and perceived professional demands, while interviews explored experiences and communication challenges in international contexts. Data were analyzed using qualitative thematic analysis to identify patterns of language needs and competency gaps. The findings indicate that English is primarily required for formal professional tasks, including participation in international meetings, report writing, document comprehension, and official correspondence. Speaking, formal writing, and mastery of technical terminology emerged as priority needs and major challenges. The study concludes that a clear gap exists between current competencies and professional communication standards. These findings highlight the importance of aligning institutional language development initiatives with international operational demands to strengthen effective global collaboration REFERENCES Armnazi, M., & Alegasan, M. (2024). Target Situation Needs Analysis of English Language Skills Required by Syrians in the Arabian Gulf Area. Indian Journal of Information Sources and Services, 14(3), 77–85. https://doi.org/10.51983/ijiss-2024.14.3.11 Franchisca, S. (2020). Designing English Course Learning Material for Grand Zuri Hotel Padang Employees. Jurnal Ilmiah Pendidikan Scholastic, 4(1), 50–55. https://doi.org/10.36057/jips.v4i1.400 Gaspar, B., & Hartanto, Y. (2019). Assessing the Design and Implementation of English Training Program for the University of Surabaya Administrative Staff. Journal of Social Sciences and Humanities, 9(1), 69–79. ojs.pnb.ac.id/index.php/SOSHUM/%0A Harry, A. (2023). Navigating the Complex Intersection of Diplomacy , Business , and Politics. 02(05), 1065–1071. https://journal.mediapublikasi.id/index.php/bullet Kholida Ziya, Rahmadi Nirwanto, & Zaitun Qamariah. (2023). The Impact Of Changes In Needs Analysis In English Learning Curriculum Development. Jurnal Bintang Pendidikan Indonesia, 1(3), 195–206. https://doi.org/10.55606/jubpi.v1i3.1693 Kurniyawan, I., Simarmata, M., & Zarzani, T. R. (2025). The Role of the National Narcotics Agency (BNN) in the Prevention and Enforcement of Narcotics Crimes. International Conference on Artificial Intelligence, Navigation, Engineering, and Aviation Technology, 2(1), 90–96. https://icaneat-apibanyuwangi.org/index.php/icaneat Lin, O., Arumugam, N., Lwin, A. S., Susanti, M., & Mohamad, F. (2021). Efficacy of the Speaking and Writing ESP Modules for Working Adults: Government Officials. International Journal of Academic Research in Business and Social Sciences, 11(3), 1484–1501. https://doi.org/10.6007/ijarbss/v11-i3/9667 Maharani, Z. C., Siagiyanto, B. E., & Refai, R. (2025). Exploring the Effectiveness of Chatgpt As a Conversational Partner on Efl Student’S Speaking Skills: a Quasi-Experimental Study in Indonesia Higher Education. Premise: Journal of English Education, 14(3), 886. https://doi.org/10.24127/pj.v14i3.12338 Meilyani, A., Rinalgi, D., Nandha, M. S., & Qamariah, Z. (2025). the Role of Needs Analysis in Designing Relevant Learning Outcomes for Efl Curriculum: Literature Review. Datokarama English Education Journal, 6(1), 32–42. https://doi.org/10.24239/dee.v6i1.113 National Narcotics Board Republic of Indonesia. (2024). Collaboration Towards Drug-Free Indonesia. In Bnn. Puspitasari, I., & Sholeha, U. I. (2025). English Education Study Program Students’ Perceptions on Improving Speaking Skills Through Litmatch. Premise: Journal of English Education, 14(2), 230. https://doi.org/10.24127/pj.v14i2.9740 Ranasinghe, R. M. S. K. (2024). Vidyodaya Journal of Humanities and Social Sciences Study of a Second-Year University English Language Teaching Programme in Sri Lanka. 09, 234–245. Rizky Vita Losi, Putra, E., Rosida, S., & Ardilla, F. (2023). Learning English At Workplace From E-Module To Improve English Proficiency Of Employees At Besilam Village. JOLADU: Journal of Language Education, 2(2), 61–68. https://doi.org/10.58738/joladu.v2i2.435 Rohmah, F. N. (2025). Exploring Teachers’ Experiences With Project-Based Learning in Online Elt: Challenges, Strategies, and Opportunities. Premise: Journal of English Education, 14(2), 336. https://doi.org/10.24127/pj.v14i2.11220 Sadapotto, A., & Hanafi, M. (2021). Designing English for Public Administration Based on Needs. Uniqbu Journal of Social Sciences, 2(April), 1–9. http://ejournal-uniqbu.ac.id/index.php/ujss/article/view/100 Suharno, S., & Suryana, D. (2025). Bridging Language Barriers in Law Enforcement: A Study on the English Language Needs of Indonesian Police Officers. Jurnal Pendidikan Progresif, 15(3), 2127–2146. https://doi.org/10.23960/jpp.v15i3.pp2127-2146 Suri, E. M., & Saripa, A. M. (2026). TOFEDU : The Future of Education Journal English for Specific Purposes ( ESP ) ( A Professional Needs Based Approach to English Language Learning ). 5(1), 830–833. https://journal.tofedu.or.id/index.php/journal Ulfah, B., Petrus, I., & Mirizon, S. (2021). ESP needs-based course design for the employees of government protocol department. English Language in Focus (ELIF), 3(2), 143–158. https://doi.org/10.24853/elif.3.2.143-158 Valensya Annisa Ikhsan, & Lilis Lamsehat Panjaitan. (2025). The Use of English as a Lingua Franca in Business Communication: A Case Study of Applied Foreign Language Students. Santhet (Jurnal Sejarah Pendidikan Dan Humaniora), 9(4), 1328–1342. https://doi.org/10.36526/santhet.v9i4.5679 Vanjinayaki, M., & Gayathri, M. (2024). Enhancing English Language Teaching through Interactive Learning Activities. Shanlax International Journal of Arts, Science and Humanities, 11(S5), 135–138. https://doi.org/10.34293/sijash.v11is5.7677 Yadav, P. (2024). Exploring The Impact Of English Language Proficiency On Cross-Cultural Communication Success. 12(3), 2320–2882. www.ijcrt.org Yusoff, M. S. B., Arifin, W. N., & Hadie, S. N. H. (2021). ABC of questionnaire development and validation for survey research. Education in Medicine Journal, 13(1), 97–108. https://doi.org/10.21315/EIMJ2021.13.1.10 Zein, O. R., Suasti, Y., & ernawati. (2022). Education Quality Improvement Through the Development of Hilda Taba’S Curriculum. International Journal of Educational Dynamics, 3(2), 61–66. http://ijeds.ppj.unp.ac.id/index.php/IJEDS Zohrabi, M. (2014). Promoting Teacher Development through an Interactive Approach to Curriculum Development. Procedia - Social and Behavioral Sciences, 98, 2025–2034. https://doi.org/10.1016/j.sbspro.2014.03.638